Early ceramic styles and technologies in the Aegean and the Balkans: - Lily Bonga (Documenta Praehistorica, 2019)
Ceramics have always played a central role in defining the Neolithic period in southeastern Europe. Early Neolithic ceramic assemblages, forming techniques, clay recipes, shapes, decoration, and vessel function have been traditionally used to establish the chronology and cultural groups of a region based on a handful of purported type-sites. This paper presents a critical review of the literature on Early Neolithic pottery in Greece, highlighting how preconceptions shaped the research and interpretation of the data of not only the ceramics themselves, but also how those interpretive conclusions were projected into other aspects of Early Neolithic life, such as the gender and status of potters and the socio-functional use of pottery. The recent reevaluation of old and new absolute dates through Bayesian analysis, statistical modelling, and stratigraphic considerations has also helped to provide a more nuanced use of relative pottery chronologies. New archaeological evidence from Northern Greece as well as reevaluations of Knossos and the Franchthi Cave are highlighted.